Catacomb Burial Structures of The Tashkent Oasis - Isabekov Behzod Imomali ogli (PhD in History) (Peerian Journals Publishing, 2024)
The catacomb graves of the Tashkent oasis are ancient burial traditions dating back to the antique and early medieval periods, widely found in Tashkent and its surrounding areas. These graves consist of long underground corridors and burial chambers, reflecting the religious beliefs and burial customs of the population of that era. Alongside the buried individuals, various luxurious items, pottery, tools, and food products were also found in these graves, enriching our knowledge of the culture and lifestyle of that time. The catacomb graves are of great significance for archaeological research, offering an opportunity to study the ancient history and cultural heritage of the Tashkent oasis
Keywords: Catacomb; Graves; Culture